AN ALTERNATIVE MEDIA OF LEARNING ARABIC LANGUAGE - Bagas Tri Nugroho; Nurul Latifatul Inayati; Mohammad Zakki Azani (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2020)
The Covid-19 pandemic has caused enormous changes in everyday life, including in the education sector. Efforts to prevent the transmission of Covid-19 are being carried out on a large scale, one of the efforts is to minimize physical contact with others and avoid crowds. This situation affects the process of teaching and learning activities in almost all schools in Indonesia. Normal learning that is usually carried out turns into distance-learning or learning online. Researchers chose Mts Muhammadiyah Waru as the research site because MTs Muhammadiyah Waru was a school that had just implemented full online learning after the pandemic. This study aims to describe the implementation of online learning and identify obstacles in the implementation of Arabic online learning at MTs Muhammadiyah Waru. This research includes field research with a qualitative approach. Data were collected through interviews, observation, and documentation. The data analysis used descriptive qualitative with inductive analysis techniques, which describes the facts obtained from the research site and then analyzed. The findings of the study showed that the implementation of Arabic learning online aims to achieve four competencies; namely to be master in writing, listening, reading, and speaking skills. Those competencies can be achieved successfully via a combination of Zoom and WhatsApp applications except for the speaking skill due to the time constraint. However, there are some obstacles in the implementation such as the readiness of the students to take part in the applications and also the disturbance that often occurs in the internet network.